THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF STUDYING ANTHROPONYMIC PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK - Abdusamadov Zafar Nurmatovich; Nazarova Sarvinoz Tavakkaljon qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
In this article, we have presented the theory and methodology of anthroponymic phraseological units in English and Uzbek. We have explored the linguistic status of anthroponymic phraseologisms in terms of their semantic structure, cognitive properties, and linguistic significance. We have also investigated how anthroponyms lose their nominative role in phraseological units and acquire generalized, symbolic, and evaluative meanings. The results of this paper show that anthroponymic phraseological units reflect national worldview, cultural memory, and value systems, and as such are a very important subject for comparative linguistics.